4DCT as first line imaging during Covid pandeminc. (1st March 2022) - Karamali, Katerina; Salau, Eniola; Das, Tilak; Scoffings, Daniel; Casey, Ruth; Masterson, Liam; Fish, Brian
Abstract: Aim: The Covid-19 pandemic encouraged prompt modification to clinical practice to minimise hospital attendances in an aim to minimize exposure and protection of the NHS whilst maintaining the standards of patient care. Current literature advocates that Four-Dimensional Computerised Tomography (4DCT) has equal diagnostic value as ultrasound alone or a combination of ultrasound and Sestamibi scan in the identification of abnormal parathyroid glands in the work up for surgical management of hyperparathyroidism. In response to the evolving pandemic at Addenbrookes we modified our practice and escalated 4DCT as our first line imaging. In light of this we had a unique opportunity to evaluate the diagnostic value of the currently used imaging modalities. Methods: This is a retrospective study of 270 parathyroidectomies who underwent pre-operative 4DCT (n=270), ultrasound (n= 254) and sestamibi scan (n=253). Subsequently, we assessed the accuracy of these three modalities with the of intra-operative findings, histology, post-operative calcium and PTH. Results: The sensitivity of the 4DCT was 77% in comparison to 43% sensitivity of the ultrasound alone. (p>0.05). The combined sensitivity of ultrasound and Sestamibi scan was found to be 69%. Conclusion: The implementation of 4DCT as a single modality diagnostic imaging can be considered equally effective and accurate in the diagnosis of parathyroid abnormality. Implementing this would reduce the number of diagnostic tests improving the likelihood of successful operative planning and reduce financial cost.